Biogas Purification up to Final Product - Yu. A. Losiuk; G. V. Orendarenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2012)
The paper considers main technological methods for biogas purification from impurities that permit to increase energy value of the product and decrease its corrosion activity.  While evaluating economic efficiency due to introduction of the corresponding purification technology, in addition, it is necessary to take into account an ecological factor.